Case-Matched Comparison of Clinical and Financial Outcome After Laparoscopic or Open Colorectal Surgery - Delaney, Conor P. (2003)
OBJECTIVE: Comparison of outcome and costs after laparoscopic and open colectomy. SUMMARY BACKGROUND DATA: Previous studies comparing laparoscopic and open colectomy report conflicting results with regard to clinical outcome and costs. METHODS: Laparoscopic colectomy patients from a prospective database were matched for age, gender, and disease-related grouping to patients who underwent the same operation by the open approach over the same period (2000 to 2001). Data for the latter group was gathered by retrospective analysis and the 2 groups were compared for outcome and direct costs. RESULTS: Laparoscopic colectomy patients (n = 150) were compared with the same number of open colectomy patients. American Society of Anesthesiologists classification (P = 0.09), body mass index (P = 0.17), diagnosis (P = 0.12), complications (P = 0.14), and rate of readmission within 30 days (P = 0.44) were similar for both groups. Operating room costs were significantly higher after laparoscopic colectomy (P < 0.0001), but length of hospital stay was significantly lower (P < 0.0001). This resulted in significantly lower total costs (P = 0.0007) owing to lower pharmacy (P < 0.0001), laboratory (P <0.0001), and ward nursing costs (P = 0.0004). CONCLUSIONS: Laparoscopic colectomy results in significantly lower direct costs compared with open colectomy for carefully matched patients.